Synthetic Cannabinoids 5F-QUPIC and MDMB-CHMICA in Plant Material – Identification and Quantification by Gas Chromatography – Mass Spectrometry (GC-MS), Nuclear Magnetic Resonance (NMR), and High-Performance Liquid Chromatography with Diode Array Detection (HPLC-DAD). (15th July 2021) - Ivanov, Ivo D.; Stoykova, Silviya S.; Burdzhiev, Nikola T.; Pantcheva, Ivayla N.; Atanasov, Vasil N.
Abstract: The synthetic cannabinoids 5F-QUPIC and MDMB-CHMICA were sprayed on plant material intended for smoking and was seized as a criminal evidence. Their presence was confirmed by gas chromatography – mass spectrometry (GC-MS), and nuclear magnetic resonance (NMR). In the absence of analytical standards (indirect approach), the quantity of 5F-QUPIC in the herbal extract was determined by high-performance liquid chromatography with diode array detection (HPLC-DAD) based on total hydrolysis and measurement of the hydrolytic product (8-hydroxyquinoline) at 292 nm. The quantity of MDMB-CHMICA was determined using the ratio of 1 H-NMR signals of both compounds in methanol-d4 . 5F-QUPIC and MDMB-CHMICA in the herbal mixture were determined by the validated HPLC-DAD protocol by a direct approach with standards.